Investigating the Mechanism of Action of Schisandra chinensis Combined with Coenzyme Q10 in the Treatment of Heart Failure Based on PI3K-AKT Pathway - Wen S; Yang K; Bai Y; Wu Y; Liu D; Wu X; Zhang X; Sun J (Dove Medical Press, 2023)
Sihua Wen,1,* Kai Yang,1,* Yunfeng Bai,2 Yanan Wu,1 Ding Liu,1 Xu Wu,1 Xiaofei Zhang,1 Jing Sun1 1Department of Pharmaceutics, The Key Laboratory of Basic and New Drug Research of Traditional Chinese Medicine, Shaanxi University of Chinese Medicine, Xianyang, People's Republic of China; 2Shaanxi Dongtai Pharmaceutical Co., Ltd, Shaanxi, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaofei Zhang; Jing Sun, Department of Pharmaceutics, College of Pharmacy, Shaanxi University of Chinese Medicine, Xianyang, People's Republic of China, Tel +86 177 7003 7322, Fax +86 029-38185333, Email 2051028@sntcm.edu.cn; sunjing202203@126.comPurpose: To study the active components, drug targets and mechanism of Schisandra chinensis (S.chinensis) combined with coenzyme Q10 (CQ10) in the treatment of heart failure (HF).Methods: Network pharmacology combined with the gene expression omnibus chip method to analyze the main pathways by which S.chinensis combined with CQ10 functioned to treat heart failure. Subsequently, the biological activities of the major pathway key proteins and their corresponding compounds were verified by molecular docking techniques. Finally, the molecular mechanism of S. chinensis combined with CQ10 for the treatment of heart failure was verified using a rat heart failure model induced by isoproterenol hydrochloride and using hematoxylin-eosin staining, TUNEL, immunohistochemistry and Western blot.Results: Network pharmacology combined with experimental validation suggests that the mechanism of action of S.chinensis combined with CQ10 in the treatment of heart failure may involve CQ10, Citral, Schisandrone, Schisanhenol B, Gomisin O, Schisandrin C and other components, which may synergistically inhibit the PI3K-AKT signaling pathway and affect the expression of AKT1, PIK3CG and other targets on this pathway. In addition, S. chinensis combined with CQ10 could effectively improve the cardiac coefficients of rats with heart failure, reduce the area of myocardial fibrosis and lowered the serum levels of IL-1β and TNF-α in heart failure rats, as well as reduced cardiac myocyte apoptosis, increased Bcl-2 expression and decreased p-PI3K/PI3K, p-AKT/AKT, P65 and Bax expression in cardiac tissue. Comparison of the results showed that the combination of S.chinensis and CQ10 was more effective compared with CQ10 alone, ie, the ability of S.chinensis combined with CQ10 in improving cardiac function, inhibiting cardiomyocyte apoptosis and reducing inflammatory response lies in the synergistic effect of PI3K/AKT signaling pathway.Conclusion: The therapeutic effect of S.chinensis combined with CQ10 on heart failure, which may occur through the inhibition of PI3K/AKT signaling pathway.Graphical Abstract: Keywords: Schisandra chinensis, coenzyme Q10, network pharmacology, molecular docking, mechanism validation, heart failure